Harold starts to simplify the expression below, as shown, but his work is not correct. –x(6x5)2(–2y6)(y) (–6x6)2(–2y6)(y) what should harold have done instead? combined like terms squared brainly

Respuesta :

squared 6x^5
and when you simplify the expression you get
72x^11y^7

Answer: He should first solve the bracket by squaring [tex](6x^5)[/tex] then multiply it by x.

Step-by-step explanation:

Here the given expression is, [tex]-x(6x^5)^2(-2y^6)(y)[/tex]

And, we can write,

 [tex]-x(6x^5)^2(-2y^6)(y)[/tex]=  [tex]-x \times 6^2 \times x^{10}\times -2y^6\times y[/tex] ( by solving the bracket)

⇒[tex]-x(6x^5)^2(-2y^6)(y)[/tex]=  [tex]-36 x^{10+1}\times -2y^{6+1}[/tex] ( Because, [tex]x^m.x^n=x^{m+n}[/tex])

⇒[tex]-x(6x^5)^2(-2y^6)(y)[/tex]=  [tex]-36 x^{11}\times -2y^7[/tex]

⇒[tex]-x(6x^5)^2(-2y^6)(y)[/tex]=  [tex]72 x^{11} y^7[/tex]



ACCESS MORE